Use of Protease from Seabass Pyloric Caeca in Combination with Repeated Freeze–Thawing Cycles Increases the Production Efficiency of Virgin Coconut Oil. Issue 5 (1st March 2019) - Patil, Umesh; Benjakul, Soottawat
Abstract : Virgin coconut oil (VCO) is separated from coconut milk using partially purified protease from seabass pyloric caeca (PPSP) in combination with different treatments including micro‐fluidization, chill–thawing, and freeze–thawing. The lowest VCO yield is obtained for coconut milk homogenized at 4000 psi, followed by hydrolysis using PPSP at the level of 5 units g −1 proteins. Conversely, the higher VCO yield is obtained from non‐homogenized and unhydrolyzed coconut milk ( p < 0.05). Coconut milk hydrolyzed by PPSP at 10 units g −1 protein, followed by freeze–thawing shows the highest yield among all the samples ( p < 0.05). VCO yield increases as chill–thawing cycles of hydrolyzed coconut milk increases up to 5 cycles ( p < 0.05). A similar trend is found in sample subjected to hydrolysis, followed by freeze–thawing. Hydrolysis by PPSP, followed by freeze–thawing of 5 cycles, yields the highest yield of VCO (98.6%). No marked difference is observed in fatty acid profile, moisture content, free fatty acid content, and oxidative stability of all VCO obtained, regardless of subsequent chill–thawing and freeze–thawing applied. All VCO samples are in the range of APCC standards. Thus, combined treatment including hydrolysis using PPSP followed by freeze–thawing (5 cycles) is a powerful method for extraction of VCO, in which high yield and prime quality could be gained. Practical Applications : In VCO production, the cost of commercial enzyme and yield of VCO are of major concern. Therefore, a cheap source of proteases, particularly fish processing byproducts, can be a promising alternative for VCO production. Additionally, a combined method, especially enzymatic hydrolysis of coconut milk followed by freeze–thawing, can be a practical process to obtain VCO with increased yield. The information on combined methods can be of benefit in manufacturing VCO with reduced cost and high yield. The use of protease from seabass pyloric caeca in combination with repeated freeze‐thawing cycles increases the production efficiency of virgin coconut oil. Abstract : The use of protease from seabass pyloric caeca in combination with repeated freeze‐thawing cycles increases the production efficiency of virgin coconut oil.